Manajemen budaya organisasi - Tasya Aspiranti (Jurnal Manajemen Bisnis Performa, 2010)
Organizational  culture  as  the  set  of  shared  values  and  norms  that  control  orga nizational   members'   interactions   with   each   other   and   with   people   outside organization. An organization's culture can be used to increase orga nizational effectiveness. This is because organizational culture controls the way members make decisions, the way interpret and manage the organizatio n's environment. In adaptif organi  zation,  organizational  culture  change  absolutely  must  be  taken  to  raise effective culture that can support organizational goals. This paper explains the importance of people in organization as organizational culture shaper, any kind theory of organizational culture, organizational culture  management and how to manage culture in organization. Some real organizational culture cases are presented in this paper and organizational culture management paradigm as conclusion is presented in the end of paper.Key words : organizational culture management